2015
DOI: 10.1186/s12936-015-0627-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound findings in pregnant women with uncomplicated vivax malaria in the Brazilian Amazon: a cohort study

Abstract: BackgroundDuring pregnancy, Plasmodium falciparum-induced malaria can cause placental lesions and intrauterine growth restriction (IUGR). There are few published studies on Plasmodium vivax-induced malaria in pregnancy. Ultrasound is an efficient method for evaluating foetal biometry and placenta. The present study aimed to investigate the occurrence of increased placental thickness, foetal biometry and the amniotic fluid via ultrasound in a cohort of pregnant women with vivax malaria in Manaus, Amazonas, Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This is a new finding. A study conducted in Brazil among pregnant women with vivax malaria reported no association of malaria and oligohydramnios [ 21 ]. However, it is worth noting that in the same study in Brazil, sonographic assessment done during the period of infection revealed thickened placentas with mal perfusion of the placentas, which may be a predisposing factor for oligohydramnios later in the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…This is a new finding. A study conducted in Brazil among pregnant women with vivax malaria reported no association of malaria and oligohydramnios [ 21 ]. However, it is worth noting that in the same study in Brazil, sonographic assessment done during the period of infection revealed thickened placentas with mal perfusion of the placentas, which may be a predisposing factor for oligohydramnios later in the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In addition, in utero exposure to malaria parasites has been associated with a decreased head circumference (HC) among fetuses and newborns, a proportional decrease in size as an outcome of the intrauterine growth retardation. 3 , 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…With the cessation of local malaria transmission in the country, disease surveillance along with entomological surveillance have been strengthened to prevent the re-introduction of malaria. The largest threat for re-introduction of malaria into the country is the importation of malaria cases from endemic countries [ 4 ]. The influx of malaria parasites into the country are through security personnel returning from United Nations peace missions, asylum seekers coming through United Nations High Commissioner for Refugees (UNHCR), foreign workforces in different trades, and local migrants going to malarious countries on travel, business or pilgrimage.…”
Section: Introductionmentioning
confidence: 99%